INTERPRETATION OF GRAVITY ANOMALY IN GEOTHERMAL FIELD ÃâÃâZÃâÃâ - HILMI AUFA (NIM : 10212057), MUHAMAD
Gravity method is one of geophysical method that used variety of density contrast from subsurface. In general, the stages of geophysical method are acquisition, data processing, and interpretation. After data acquisition is done with gravimeter, gravity data is corrected by tidal, drift, latitude, and elevation correction to get complete bouguer anomaly. To do qualitative interpretation, Separation is done to become regional and residual anomaly, and also with gradient analysis method. Meanwhile in quantitative interpretation is done by forward modeling (Talwani). From geothermal field ‘Z’ data, maps which is produced can delineat geology structures. There is a depression zone in the middle of research area which is zone with low topoghapy level such a lengthwise from north west-south east and also deep, which can be confirmed by regional and vertical derivative maps. Model is constructed with 3 layer of rocks assumption with density 2,2 gr/cm3, 2,5 gr/cm3, dan 2,67 gr/cm3 which the variation of density per depths is fit with field data.